Reinforcing cement bricks with different reinforcement methods for load-bearing walls in Libya (Sebha University Conference Proceedings, 2024)
The construction of load-bearing wall systems has become widespread in Libya in a large number of buildings made of various building materials, including cement bricks and limestone. Most of these buildings are made of brick materials that are less deteriorating than reinforced concrete, especially in hot environments. This type of construction is found in many regions and the reason for its spread is the lack of costs and availability of materials. The research aims to study the use of different methods to reinforce bricks and the behavior of cement bricks inducing the effect of regular vertical loads, knowing the efficiency of bricks reinforced with steel, and thinking about replacing steel rods with PPR plastic rods. The latter was armed with electrical pipes. Filling the bricks with injection mortar only in order to support the buildings under construction with the best type of reinforcement. Obtaining a strong wall capable of resisting a lot of stress for a long period of time. A laboratory study was conducted on the cement bricks used in Libya, where the cement bricks were reinforced by reinforcing them using steel rods, PPR plastic rods, and electrical plastic rods. The voids of the cement bricks were filled with injection mortar only, without reinforcement, and a pressure resistance test was conducted on these various bricks, with quality control tests being carried out. On the materials included in the bricks. Among the results of this study are non-load-bearing cement bricks manufactured in Libya. The results showed that the injection mortar reinforcement system demonstrated remarkable efficiency with reinforcing steel and gave the best results in cement brick reinforcement due to its clear effect in increasing pressure resistance and the possibility of using it in load-bearing walls. Also, reinforcement of bricks with PBR pipes had good results compared to steel reinforcement. This calls for continuing research and expanding laboratory experiments, including the possibility of using layers of fiberglass or iron mesh on both sides of cement bricks to reinforce existing buildings.